Determinants and prognostic implication of improved left ventricular ejection fraction in chronic heart failure patients with reduced ejection fraction. (25th November 2020) - Hu, K; Schregelmann, L; Liu, D; Lengenfelder, B; Ertl, G; Frantz, S; Nordbeck, P
Abstract: Background: Previous studies have demonstrated that left ventricular ejection fraction (LVEF) is not associated with overall survival in patients with chronic heart failure (CHF). This study aimed to examine if improved EF is associated with better survival in these patients. Methods: Study subjects were selected from the database in the REDEAL trial, which included all patients with CHF and a LVEF of <50% referred to our hospital between 2009 and 2017. Of these, 902 patients completed at least twice echocardiography examinations (BL and FUP) at a minimal interval of 12 [median 17 (14–25)] months. Results: At baseline, there were 522 patients with BL_EF >35% (aged 68±12 years, male 74.5%, median EF 44%) and 381 patients with BL_EF ≤35% (aged 65±13 years, male 74.5%, median EF 29%). Survival was similar between groups (76.6% vs. 73.8%, P=0.322). Over a median echocardiography follow-up of 17 months, FUP_ EF increased by 1.3% (−4.0–8.0%) in the subgroup of BL-EF>35% and increased by 11.0% (2.0–20.0%) in the subgroup of BL_EF≤35%. Survival analysis showed that absolute change in EF was significantly associated with survival in the subgroup of BL_EF≤35% but not in the subgroup of BL_EF>35%. Therefore, further analysis was conducted among patients in the subgroup of BL_EF≤35%. In this subset of BL_EF≤35%, improved EF was defined as a FUP_EF of >40%. 171 (44.9%) patients presented with improved EF, EF remained unchanged or reduced in the rest 210 patients (55.1%, FUP_EF≤40%). Patients with improved EF was associated with better survival over a median clinical follow-up of 19 (11–32) months (80.7% vs. 68.1%, P=0.001). Multivariable Cox regression analysis showed that improved EF remained an independent determinant of overall survival after adjusted for potential clinical covariates including age, sex, diabetes, hyperuricemia, renal dysfunction, coronary artery bypass grafting, sleep-disordered breathing, and prior ICD or CRT_D implantation (HR 0.59, 95% CI 0.38–0.91, P=0.018). In this subgroup of BL_EF≤35%, age and sex-independent determinants of improved EF included without prior myocardial infarction (OR 0.40, 95% CI 0.24–0.67, P<0.001), without ICD or CRT-D implantation (OR 0.32, 95% CI 0.17–0.61, P=0.001), and smaller LV end-diastolic diameter (OR=0.94, 95% CI 0.90–0.99, P=0.012). Conclusions: Longitudinal improvement in LVEF is significantly associated with survival benefit in the subgroup of baseline EF≤35% but not in the subgroup of baseline EF>35%. In the subgroup of baseline EF≤35%, improved LVEF remains an independent determinant of survival benefit Determinants of improved LVEF in HF patients with baseline EF≤35% include without myocardial infarction, without ICD implantation, and smaller LV chamber at baseline. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This work was supported by the German Federal Ministry of Education and Research